Think Piece: Reflections on the Individual-Collective Relation in Change Agency Formation in the Samsø Renewable Energy Island Project - Monica Carlsson (Environmental Association of Southern Africa, 2018)
This paper offers reflections on change agency formation in the Renewable Energy Island (REI) project on Samsø, following a field visit to the island in June 2016. Both individual and collective agency are set out as central for the processes leading to the change in the REI project, spurring reflections on individual-collective agency dimensions in change agency formation related to climate change issues, inspired by notions of participation in everyday life (Marres, 2011; Micheletti 2002, 2006). The paper furthermore focuses on an exploration of two different formats of knowledge-sharing in the learning processes leading to change on Samsø - 'neighbourly visits' and web-based documentation - emphasising the role of knowledge in change agency formation. Drawing on Jamison's (2001, 2010) notion of the making of green knowledge in the tension between environmental politics and cultural transformation, the paper suggests that the REI project can be characterised by both an adaptive approach and by social resilience development.